An Extensive Circuitry for Cell Wall Regulation in Candida albicans - Blankenship, Jill R. (Public Library of Science, 2010)

(untitled)
Protein kinases play key roles in signaling and response to changes in the external environment. The ability of Candida albicans to quickly sense and respond to changes in its environment is key to its survival in the human host. Our guiding hypothesis was that creating and screening a set of protein kinase mutant strains would reveal signaling pathways that mediate stress response in C. albicans. A library of protein kinase mutant strains was created and screened for sensitivity to a variety of stresses. For the majority of stresses tested, stress response was largely conserved between C. albicans, Saccharomyces cerevisiae, and Schizosaccharomyces pombe. However, we identified eight protein kinases whose roles in cell wall regulation (CWR) were not expected from functions of their orthologs in the model fungi Saccharomyces cerevisiae and Schizosaccharomyces pombe. Analysis of the conserved roles of these protein kinases indicates that establishment of cell polarity is critical for CWR. In addition, we found that septins, crucial to budding, are both important for surviving and are mislocalized by cell wall stress. Our study shows an expanded role for protein kinase signaling in C. albicans cell wall integrity. Our studies suggest that in some cases, this expansion represents a greater importance for certain pathways in cell wall biogenesis. In other cases, it appears that signaling pathways have been rewired for a cell wall integrity response.